Data in online database ‘Last Statues of Antiquity (LSA)’ - Smith, R; Ward-Perkins, B; Worth, J (University of Oxford, 2017)
This dataset represents the text and image data contained in the searchable database of the published evidence for statuary and inscribed statue bases set up after AD 284, that were new, newly dedicated, or newly re-worked. (This database was completed and made public in May 2012, with only some minor revisions thereafter). The deposit includes data for a small number of records that are not included in the public version, and the contents of some notes fields. Researchers are welcome to use the data for their own purposes but should acknowledge the original source, and re-use should not be for commercial purposes. Meanwhile, enquiries should go to LSA@classics.ox.ac.uk.